Utilizing the right phosphor in near-ultraviolet and blue light-emitting diode devices to generate white illumination - Dieu An Nguyen Thi; Nguyen Doan Quoc Anh; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In the scenario of solid-state lighting (SSL) gradually replacing old standard techniques; the pc-LEDs (or diodes based on conversion phosphor) becomes a common method for creating white illumination, based on SSL. As of now, both of the UV-LEDs and the blue LEDs have been still being considered for the task of creating white illumination through phosphor excitation as it hasn’t been known which LED type is truly superior. It is common that when it comes to phosphor, people will overlook the performance in LED devices with a wavelength range of 365 nm to 470 nm. Our research demonstrates the information concerning extrinsic quantum efficacy in the InxGa1-xN LED devices with the mentioned range as well as combines the information and the effectiveness of phosphor for the task of examining the performance of near-UV and blue LEDs and creating white illumination. In addition, the research demonstrates recreations for the task of assessing the white illumination mixtures under the correlated color temperature of 3000 K and 4000 K in the two LED structures.